Penerapan Terapi Dzikir Terhadap Skala Nyeri pada Pasien Post Operasi di RSUD Bagas Waras Klaten - Rangga Baskara Jiwa Negara; Irma Mustika Sari (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Background: Surgical procedures can be a potential or actual threat to a person's integrity that can evoke physiological and psychological reactions. Based on WHO 2022, patients with surgery are recorded at 234 million people. The problem caused by surgery or surgery is pain. Pain management can be done by pharmacological or non-pharmacological methods. The application of dhikr therapy can be used as a non-pharmacological therapy to be combined with pharmacological therapy so that person's pain scale can be further reduced. Objective: Describe results the implementation of dhikr therapy on post-operative patients at RSUD Bagas Waras Klaten. Method: Application of Dhikr Therapy to the Pain Scale in Post-operative Patients with descriptive method was carried out for 3 days in 1 day there were 2 sessions with each session 10 minutes and interval between each session was given 2 hours. Results: There was decrease in the pain scale in 2 post-operative patients, after applying dhikr therapy for 3 days from a controlled severe pain scale to mild pain scale. Conclusion: The results the application of Dhikr Therapy for 3 consecutive days can reduce the pain scale in post-operative patients at RSUD Bagas Waras Klaten.